2019
DOI: 10.1111/ijlh.13089
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning applications in the diagnosis of leukemia: Current trends and future directions

Abstract: Augmented human intelligence (AHI) and artificial intelligence (AI) tools might shape the future of medical practice. The expansion of data generated by our systems, medical literature, and the inefficiencies of healthcare systems will necessitate utilizing the power of AI tools. 1,2 The integration of AHI tools into medical practice, including machine learning (ML) and deep learning algorithms, has begun. For instance, the United States food and drug administration (US-FDA) has approved many AI-based software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 51 publications
2
48
0
Order By: Relevance
“…Recently, investigators have been applying unsupervised methods to minimize the need for manual segmentation and feature extraction, which are time consuming tasks for operators, particularly in hematology and cytology. This is in line with conducting studies to apply ML in the hematopathology field [38].…”
Section: Digital Pathology For the Diagnosis Of Acute And Chronic Leusupporting
confidence: 72%
“…Recently, investigators have been applying unsupervised methods to minimize the need for manual segmentation and feature extraction, which are time consuming tasks for operators, particularly in hematology and cytology. This is in line with conducting studies to apply ML in the hematopathology field [38].…”
Section: Digital Pathology For the Diagnosis Of Acute And Chronic Leusupporting
confidence: 72%
“…This compliments other novel AI strategies aimed at utilizing mutational and peripheral blood data for more accurate MPN diagnosis, 30 along with improved interpretation of peripheral blood/bone marrow smear preparations. [31][32][33][34] Secondly, a comprehensive and easily interpreted summary of the megakaryocytic population will enable the pathologist to concentrate on the "higher-level" process of integrating the broader pathological features with the clinical and laboratory findings. Thirdly, this approach is ideally suited for more accurate assessment of sequential specimens from patients undergoing treatment and/or repeated investigation, in whom quantitative morphological correlates of disease response are currently unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…ML is increasingly used in the medical community, particularly in the field of oncology. Previous studies have demonstrated that ML models can provide better accuracy and discrimination for the prediction of prognoses for lung adenocarcinoma (12) and breast cancer (13), chemoradiation therapy response in rectal cancer (14), radiotherapy response for acromegaly (15), surgical outcomes for head and neck cancer (16), and diagnosis for leukemia (17). For sellar region tumors, ML could be more effective for predicting a patient's clinical outcome and could provide better clinical decision support for neuroendocrinologists and neurosurgeons (18).…”
Section: Introductionmentioning
confidence: 99%